2020
DOI: 10.1186/s12913-020-4974-4
|View full text |Cite
|
Sign up to set email alerts
|

The societal economic burden of autosomal dominant polycystic kidney disease in the United States

Abstract: Background: Autosomal dominant polycystic kidney disease (ADPKD) is one of the most common inherited kidney diseases characterized by progressive development of renal cysts and numerous extra-renal manifestations, eventually leading to kidney failure. Given its chronic and progressive nature, ADPKD is expected to carry a substantial economic burden over the course of the disease. However, there is a paucity of evidence on the impact of ADPKD from a societal perspective. This study aimed to estimate the direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The recent Food and Drug Administration (FDA) approval of disease-modifying therapy for ADPKD patients at risk of rapid progression will help support the complex management of these high-risk patients [31]. Timely identification of these patients is of utmost importance as initiating treatment has been shown to slow the rate of decline in kidney function [32], which may help to reduce the substantial burden associated with ADPKD [33].…”
Section: Discussionmentioning
confidence: 99%
“…The recent Food and Drug Administration (FDA) approval of disease-modifying therapy for ADPKD patients at risk of rapid progression will help support the complex management of these high-risk patients [31]. Timely identification of these patients is of utmost importance as initiating treatment has been shown to slow the rate of decline in kidney function [32], which may help to reduce the substantial burden associated with ADPKD [33].…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the fact that the US spent many research grants on PKD. A study [29] reported that the estimated total annual costs attributed to ADPKD in 2018 ranged from $7.3 to $9.6 billion in sensitivity analyses, equivalent to $51,970 to $68,091 per individual with PKD. There were 37 journals in the T100PKDs.…”
Section: Dominant Countries and Journals On Pkdmentioning
confidence: 99%
“…Unrelenting cyst growth causes kidney enlargement and functional decline, associated with hypertension, cyst hemorrhage, gross hematuria, nephrolithiasis, cyst infection, pain, and reduced quality of life. The total annual costs attributed to ADPKD in the United States were estimated to be $7.3 to $9.6 billion in 2018 (Cloutier et al, 2020). Direct healthcare costs accounted for $5.7 billion (78.6%), mostly driven by renal replacement therapy ($3.2 billion; 43.3%).…”
Section: Introductionmentioning
confidence: 99%